The role of five big personality traits and entrepreneurial mindset on entrepreneurial intentions among university students in Saudi Arabia - Al-Ghazali, Basheer M.; Shah, Syed Haider Ali; Sohail, M. Sadiq (Frontiers in Psychology, 2022)
The big five personality traits and entrepreneurial Mindset are crucial individual-level elements that determine entrepreneurial intention. This study examines the impact of big five personality traits and entrepreneurial mindset, on entrepreneurial intention using the theory of planned behaviour. Besides, this study examined the role of entrepreneurial self-efficacy and attitude toward entrepreneurship influences entrepreneurial intention. To achieve the research objectives, a quantitative approach was used. Structural equation modeling (SEM) and path analysis were conducted using SmartPLS software. Data were collected from 270 respondents through online questionnaires. Findings of the study revealed that big five personality traits influence entrepreneurial self-efficacy and attitude toward entrepreneurship which led to entrepreneurial intention. Finally, the moderating role of entrepreneurial passion also found to have strong effect on influence entrepreneurial self-efficacy and attitude toward entrepreneurship. This study offers evidences and insights that academics, educators, and others involved in the creation or expansion of entrepreneurial knowledge can use as a reference point.